The historical context of grave 58 (G58) from the Sināw area (al-Sharqiyyah, Sultanate of Oman): a warrior during the Samad Late Iron Age? (poster) - Mauro, Fausto (Proceedings of the Seminar for Arabian Studies, 2018)
This paper presents grave 58 (G58) and its archaeological context brought to light during the rescue excavations in the Sināw area (al-Sharqiyyah region, Sultanate of Oman) carried out by an Italian team in 2014 in the Sināw-Maḥawt-Duqm Road network. The activities were supported and promoted by the Ministry of Heritage and Culture and the Ministry of Transport and Communications of the Sultanate of Oman. Several funerary structures arranged in six sectors were excavated, all of them attributable to a time spanning the Early Bronze Age to the Samad Late Iron Age (c.3100 BC to AD 300). G58 was discovered among these graves. It is a pit grave containing a single male crouched on his right side. The burial has yielded a rich array of grave-goods, including an iron sword with a distinctive hooked grip bordered with silver and inlaid with ivory and wood, two iron daggers, one bronze ring, one hemispherical bronze bowl, and three organic remains. In addition, two other pits (G50 and G59) were found close to G58 and containing kneeling dromedaries. The burials seem to reflect the prestigious role of the individual in a tribal community. Furthermore, the ivory on the hooked grip attests to the south-eastern Arabia trade in the Indian Ocean during the Samad Late Iron Age.